Irony and Its Representations in Postmodern Arts - Allawi Mserbit, Hamza; Talib Jaafar, Ihsan (International Journal of Psychosocial Rehabilitation, 2020)
The paper dealt with irony and its representations in postmodernist drawings and studied the nature of satire and the mechanisms involved in postmodern art. The research consists of four chapters: The first chapter dealt with the methodological framework, including the research problem, which is determined by answering the following question: What are the representations of irony in postmodernist drawings? It included the importance of research and the need for it. As for the aim of the research, it was "to reveal the mockery and its representations in postmodernism drawings," while the limits of the research were limited to studying the mockery and its representations in the postmodernist fees for the years (1962-2007). As for the second chapter, it included two topics: the first dealt with the concept of mockery, and the second topic, address irony in postmodern arts. Whereas the third chapter included the research community and the research sample, the researcher used the content analysis tool, the tool stability factor, and the validity of the tool, and then he used statistical means. As for the fourth chapter, it deals with reviewing the research results, including the irony in postmodern arts (pop art, body art, and graffiti art) having a close relationship with the artist's psychology, which influenced the artist's ability to achieve his satirical forms. Irony in postmodern art has also been associated with inciting protest, marginalizing society, rejecting social reality, and opposing old methods. The researcher also reached a number of conclusions, including that irony plays an important role in ridding people of tension of all kinds. Irony is the mirror that reflects the concerns of society.